The shepherd of weeds - Appelbaum, Susannah (Knopf, 2011)
With an army of scarecrows, a legion of birds, and her friends and uncle by her side, it is up to Ivy Manx to wage war against the evil Vidal Verjouce and the Tasters Guild, defeat her own father, and restore order to the plant world.